Socioeconomic and cognitive roots of trait anxiety in young adults - Cermakova, Pavla; Chlapečka, Adam; Andrýsková, Lenka; Brázdil, Milan; Marečková, Klára (Social cognitive and affective neuroscience, 2022)
In 54 participants (41% women) from the Czech arm of the European Longitudinal Study of Pregnancy and Childhood, a national birth cohort with prospectively collected data from their birth until young adulthood, we aimed to study the association between early-life socioeconomic deprivation (ELSD), cognitive ability in adolescence, trait anxiety and resting state functional connectivity of the lateral prefrontal cortex (LPFC) in young adulthood. We found that ELSD was associated with lower cognitive ability in adolescence (at age 13) as well as higher trait anxiety in young adulthood (at age 23/24). Higher cognitive ability in adolescence predicted lower trait anxiety in young adulthood. Resting state functional connectivity between the right LPFC and a cluster of voxels including left precentral gyrus, left postcentral gyrus and superior frontal gyrus mediated the relationship between lower cognitive ability in adolescence and higher trait anxiety in young adulthood. These findings indicate that lower cognitive ability and higher trait anxiety may be both consequences of socioeconomic deprivation in early life. The recruitment of the right LPFC may be the underlying mechanism, through which higher cognitive ability may ameliorate trait anxiety.
Keywords: dospělí; birth cohort; Longitudinal Studies; ženské pohlaví; mladiství; Socioeconomic Factors; lidé; Magnetic Resonance Imaging; cognition; Cognition; mladý dospělý; Child; Brain; dítě; trait anxiety; Humans; epidemiology; mužské pohlaví; Adult; socioekonomické faktory; Male; magnetická rezonanční tomografie; kognice; mozek; Young Adult; Adolescent; úzkost; Anxiety; Female; longitudinální studie